Functional carbon fiber for orthopedic implants, preparation method thereof, and composite material for implants containing the same and preparation method thereof
By adding carboxylated carbon nanotubes to the CFR-PEEK composite material and subjecting electron beam irradiation to form a crosslinked structure, the composite material has insufficient impact strength and toughness, poor biocompatibility and susceptibility to infection in orthopedic implants, and the improvement of high toughness, antibacterial and osteointegration capabilities has been achieved.
Patent Information
- Application Number
- CN202211663176.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-23
AI Technical Summary
The existing CFR-PEEK composites have problems in orthopedic implants that have poor impact strength and toughness, biological inertia are not conducive to cell growth and adhesion, insufficient osteogenesis integration capabilities, and prone to bacterial infections.
By adding carboxylated carbon nanotubes to the sizing agent and subjecting electron beam irradiation to form a crosslinked structure, the toughness and conductivity of the composite material are improved, while enhancing antibacterial, osteoinduction and osteointegration capabilities.
It improves the impact strength and toughness of the composite materials for orthopedic implants, enhances its antibacterial and osseous integration capabilities, improves biocompatibility, and reduces the risk of bacterial infection.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical devices, and in particular relates to a functional carbon fiber for orthopedic implants, a preparation method thereof, and a composite material for implants containing the functional carbon fiber and a preparation method thereof. Background Art
[0002] Carbon fiber reinforced polyetheretherketone (CFR-PEEK) has become the most promising hard tissue repair material that can replace traditional metal implants due to its excellent thermal stability, mechanical properties, radiolucency, and biocompatibility. Unlike typical metal materials with a high elastic modulus of more than 100 GPa, carbon fiber reinforced polyetheretherketone (CFR-PEEK) with different fiber lengths and orientations has an adjustable elastic modulus close to cortical bone (~20 GPa), which can reduce the risk of osteoporosis and bone resorption caused by stress shielding due to elastic mismatch between implants and human bones.
[0003] However, CFR-PEEK composite materials still have the problem of poor impact strength and toughness. At the same time, the biological inertness of CFR-PEEK composite materials is not conducive to cell growth and adhesion, and its inferior osteogenic integration ability prevents it from forming a strong bond with human bone tissue after implantation into the human body, thereby affecting the long-term stability of the implant material in the human body. In addition, CFR-PEEK implant surgery will inevitably encounter bacterial infection during the operation and postoperative recovery process. In order to avoid bacterial infection, antibiotics are usually used to prevent bacterial infection and reduce the chance of inflammation. Antibiotics are widely used clinically to reduce the morbidity and mortality of pathogenic bacterial infections. However, long-term abuse of antibiotics will make many pathogens easily resistant to various antibiotics, which will lead to the long-term treatment of pathogen-infected diseases and reduce the treatment effect, and even lead to the deterioration of the patient's condition or even death. Summary of the invention
[0004] The purpose of the present invention is to provide a functional carbon fiber for orthopedic implants, a preparation method thereof, and a composite material for implants containing the same and a preparation method thereof. The carbon fiber composite material in the present invention has high impact strength, good toughness, and has antibacterial, bone-inducing, and bone-integrating capabilities.
[0005] The present invention provides a method for preparing functional carbon fiber for orthopedic implants, comprising the following steps:
[0006] A) forming a stable carboxylated carbon nanotube aqueous dispersion of the carboxylated carbon nanotubes;
[0007] B) adding the carboxylated carbon nanotube aqueous dispersion obtained in step A) to a polyamic acid aqueous solution having a pH value of 6.5 to 7 to obtain a sizing agent;
[0008] C) After the carbon fiber is impregnated in a sizing agent, it is dried by three-stage hot rollers and hot air, and the dried carbon fiber is thermally imidized to obtain sized carbon fiber;
[0009] D) irradiating the sized carbon fibers to obtain functional carbon fibers for orthopedic implants.
[0010] Preferably, the polyamic acid aqueous solution with a pH value of 6.5 to 7 is prepared according to the following steps:
[0011] In a reaction container with a nitrogen protection device, diamine and dianhydride are mixed in a molar ratio of 1:(0.9-1.1) and then mixed with a solvent, and stirred at 0-10° C. for 1-2 hours; the obtained solution is freed of the solvent to obtain polyamic acid, the polyamic acid is added into deionized water and stirred, an organic amine is added, and the pH value is adjusted to 6.5-7 to obtain a polyamic acid aqueous solution;
[0012] The diamine has a structure shown in Formula I and / or Formula II:
[0013]
[0014] The dianhydride has a structure shown in Formula III:
[0015]
[0016] Preferably, the mass ratio of the polyamic acid, the carboxylated carbon nanotube aqueous dispersion and deionized water is 1:(0.5-2):(80-120).
[0017] Preferably, the average diameter of the carbon fibers in step C) is 4 to 8 μm.
[0018] Preferably, the temperatures of the three-stage hot rollers are 75-85°C, 85-95°C, and 105-115°C, respectively.
[0019] Preferably, the thermal imidization is a three-stage programmed temperature increase, wherein the temperature of the first stage thermal imidization is 80-120°C; the temperature of the second stage thermal imidization is 180-220°C; and the temperature of the third stage thermal imidization is 280-320°C;
[0020] The irradiation treatment in step D) is electron beam irradiation treatment, the energy of the electron beam irradiation is 50-200kev, and the dose of the electron beam irradiation is 0.1-1kGy.
[0021] The present invention provides a functional carbon fiber for orthopedic implants, which is prepared according to the preparation method described above.
[0022] The present invention provides a method for preparing a carbon fiber / polyetheretherketone composite material for an implant, comprising the following steps:
[0023] S1) compounding the polyaryletherketone with the functional carbon fiber for orthopedic implants prepared by the preparation method or the functional carbon fiber for orthopedic implants by a melt impregnation method to obtain a carbon fiber polyaryletherketone prepreg;
[0024] S2) processing and molding the carbon fiber polyaryletherketone prepreg to obtain a carbon fiber / polyetheretherketone composite material for an implant.
[0025] Preferably, the mass ratio of the functional carbon fiber for orthopedic implants to polyaryletherketone is 1:(1-3);
[0026] The melt index of the polyaryletherketone is 50 to 200 g / 10 min.
[0027] The present invention provides a carbon fiber / polyetheretherketone composite material for an implant, which is prepared according to the preparation method described above.
[0028] The orthopedic composite material prepared by the present invention has the following advantages:
[0029] In the present invention, carboxylated carbon nanotubes are added to the sizing agent, and the carbon in the carboxylated carbon nanotubes after electron beam irradiation is partially hybridized by sp 2 becomes sp 3 , so that adjacent carboxylated carbon nanotubes are cross-linked, and carboxylated carbon nanotubes can also be cross-linked with carbon fibers to a certain extent, so that a bridge structure can be formed between carbon fibers, thereby improving the toughness of the composite material. At the same time, the introduction of carboxylated carbon nanotubes improves the conductivity of the composite material, can eliminate the influence of accumulated charge on ion injection, and enhance the ion injection capacity of the material. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing functional carbon fiber for orthopedic implants, comprising the following steps:
[0031] A) forming a stable carboxylated carbon nanotube aqueous dispersion of the carboxylated carbon nanotubes;
[0032] B) adding the carboxylated carbon nanotube aqueous dispersion obtained in step A) to a polyamic acid aqueous solution having a pH value of 6.5 to 7 to obtain a sizing agent;
[0033] C) After the carbon fiber is impregnated in a sizing agent, it is dried by three-stage hot rollers and hot air, and the dried carbon fiber is thermally imidized to obtain sized carbon fiber;
[0034] D) irradiating the sized carbon fibers to obtain functional carbon fibers for orthopedic implants.
[0035] The present invention firstly pretreats the carbon nanotubes to prepare a stable carboxylated carbon nanotube dispersion.
[0036] In the present invention, the preparation method of the carboxylated carbon nanotubes can be carried out with reference to CN114031710B. The present invention first mixes carbon nanotubes with nitric acid solution, reacts under heating and ultrasonic conditions, then cools the product to room temperature, filtrates, washes and then dries to obtain carboxylated carbon nanotubes of different contents; specifically, in an embodiment of the present invention, the preparation can be carried out according to the following steps: first, carbon nanotubes are mixed with nitric acid solution, the mass ratio of carbon nanotubes to nitric acid is 1:300, and the concentration of nitric acid is 1 mol / L. Heat to 55°C and react under ultrasonic conditions at an ultrasonic power of 150W for 1 to 2 hours, then cool the product to room temperature, filtrate, wash and then dry to obtain carboxylated carbon nanotubes.
[0037] In the present invention, the carbon nanotubes are preferably single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and the length of the carbon nanotubes is greater than 2 μm, the diameter is 10 to 30 μm, and the purity is greater than 97%.
[0038] In the present invention, the concentration of the nitric acid solution is 1 to 3 mol / L, preferably 1 to 2 mol / L.
[0039] In the present invention, the mass ratio of the carbon nanotubes to the nitric acid is 1:250-350, more preferably 1:200-300.
[0040] In the present invention, the heating temperature is 50-60°C, preferably 53-58°C, such as 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, preferably a range value with any of the above values as the upper or lower limit; the ultrasonic power is 80-150W, preferably 100-120W, such as 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, preferably a range value with any of the above values as the upper or lower limit. The ultrasonic frequency is 30-45kHz, preferably 35-40kHz, such as 30kHz, 31kHz, 32kHz, 33kHz, 34kHz, 35kHz, 36kHz, 37kHz, 38kHz, 39kHz, 40kHz, 41kHz, 42kHz, 43kHz, 44kHz, 45kHz, preferably with any of the above values as the upper or lower limit of the range value; the reaction time is 1 to 3 hours, more preferably 1 to 2 hours.
[0041] The obtained carboxylated carbon nanotubes are mixed with water, subjected to ultrasonic dispersion treatment and then centrifuged to remove the carbon nanotubes agglomerated at the bottom to obtain a stable carboxylated carbon nanotube aqueous dispersion.
[0042] In the present invention, the ultrasonic dispersion time is 3 to 10 minutes, preferably 5 to 8 minutes; the concentration of the carboxylated carbon nanotube aqueous dispersion is 0.001 to 0.01 g / mL, preferably 0.005 to 0.008 g / mL, such as 0.001 g / mL, 0.002 g / mL, 0.003 g / mL, 0.004 g / mL, 0.005 g / mL, 0.006 g / mL, 0.007 g / mL, 0.008 g / mL, 0.009 g / mL, 0.01 g / mL, preferably a range value with any of the above values as the upper or lower limit.
[0043] After obtaining a stable carboxylated carbon nanotube aqueous dispersion, the present invention prepares a sizing agent according to the following steps:
[0044] The diamine and the dianhydride are mixed with a solvent, stirred for reaction, the solution after the reaction is heated to 60-80° C., and the solvent is removed by distillation under reduced pressure to obtain a polyamic acid;
[0045] The polyamic acid is mixed with water, an organic amine is added to adjust the pH value of the solution to 6.5-7, and then the carboxylated carbon nanotube aqueous dispersion prepared above is added to obtain a sizing agent.
[0046] In the present invention, the diamine has a structure shown in Formula I and / or Formula II:
[0047]
[0048] The dianhydride has a structure shown in Formula III:
[0049]
[0050] In the present invention, the solvent is one or more of dimethylacetamide (DMAC), N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP); the molar ratio of the diamine to the dianhydride is preferably 1:(0.9-1.1), more preferably 1:1; the ratio of the total mass of the diamine and the dianhydride to the mass of the solvent is 1:(40-60), preferably 1:50.
[0051] In the present invention, the reaction temperature is 0-10°C, preferably 1-9°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, preferably a range value with any of the above values as the upper or lower limit; the reaction time is preferably 1-2 hours.
[0052] In the present invention, the temperature of the reduced pressure distillation is 60-80°C, preferably 65-75°C, such as 60°C, 65°C, 70°C, 75°C, 80°C, preferably a range value with any of the above values as the upper or lower limit.
[0053] In the present invention, the organic amine is preferably one or more of isopropylamine, triethylamine and diethylamine; the present invention does not specifically limit the amount of the organic amine, as long as the pH value of the system can be adjusted to the required range. The organic amine can be complexed with the polyamic acid to form a salt to increase the stability in the aqueous solution.
[0054] In the present invention, the mass ratio of the polyamic acid, the carboxylated carbon nanotube aqueous dispersion and deionized water is 1:(0.5-2):(80-120), preferably 1:(1-1.5):(100-110).
[0055] After obtaining the sizing agent, the present invention uses a sizing device with three-stage hot rollers and hot air drying to size the unidirectional carbon fiber. The present invention first immerses the carbon fiber in a sizing tank with a sizing agent for impregnation treatment, and then the carbon fiber impregnated in the sizing tank is rolled up after passing through three-stage hot rollers and hot air drying. The dried carbon fiber is placed in a vacuum furnace for thermal imidization to obtain sized carbon fiber.
[0056] In the present invention, the unidirectional carbon fiber tow is one of 1K, 3K, 6K, and 12K, preferably 3K; the strength of the unidirectional carbon fiber is one or more of T300, T600, and T800, preferably T800; in the present invention, the carbon fiber is a carbon fiber that has not been sizing treated; the diameter of the carbon fiber is 4 to 8 μm, preferably 5 to 7 μm. The present invention also has no specific restrictions on the carbon fiber manufacturer.
[0057] In the present invention, the immersion time is 1 to 5 seconds, preferably 2 to 4 seconds. The temperatures of the three-stage hot rollers are 80°C, 90°C, and 110°C respectively; the hot air drying temperature is 150°C to 200°C, preferably 180°C to 190°C, such as 150°C, 160°C, 170°C, 180°C, 190°C, and 200°C, preferably a range value with any of the above values as the upper or lower limit.
[0058] In the present invention, the thermal imidization is a three-stage programmed temperature rise, wherein the temperature of the first stage of thermal imidization is 80-120°C, preferably 90-110°C, such as 80°C, 90°C, 100°C, 110°C, 120°C, preferably a range value with any of the above values as the upper or lower limit; the time of the first stage of thermal imidization is 0.5-2 hours, preferably 1-1.5 hours; the temperature of the second stage of thermal imidization is 180-220°C, preferably 190-210°C, such as 180°C, 190°C, 20 0℃, 210℃, 220℃, preferably a range value with any of the above values as the upper or lower limit; the time of one stage of thermal imidization is 0.5 to 2 hours, preferably 1 to 1.5 hours; the temperature of the three stages of thermal imidization is 280 to 320℃, preferably 290 to 310℃, such as 280℃, 290℃, 300℃, 310℃, 320℃, preferably a range value with any of the above values as the upper or lower limit; the time of one stage of thermal imidization is 0.5 to 2 hours, preferably 1 to 1.5 hours.
[0059] In the present invention, the irradiation is electron beam irradiation, and the electron beam output energy is 50-200kev, preferably 100-150kev, such as 50kev, 60kev, 70kev, 80kev, 90kev, 100kev, 110kev, 120kev, 130kev, 140kev, 150kev, 160kev, 170kev, 180kev, 190kev v, 200kev, preferably a range value with any of the above values as the upper or lower limit; the irradiation dose is 0.1-1kGy, preferably 0.3-0.8kGy, such as 0.1kGy, 0.2kGy, 0.3kGy, 0.4kGy, 0.5kGy, 0.6kGy, 0.7kGy, 0.8kGy, 0.9kGy, 1kGy, preferably a range value with any of the above values as the upper or lower limit.
[0060] The present invention uses electron beam irradiation to generate certain crosslinking between the carboxylated carbon nanotubes, polyamic acid and carbon fibers added to the sizing agent. After the electron beam (part of the carbon in the irradiated carbon nanotubes is hybridized by sp 2 becomes sp 3 , adjacent carbon nanotubes are cross-linked, and the functional groups such as carboxyl on the surface of functionalized carbon nanotubes can also participate in the imidization heat buckle process, thereby forming a bridge structure between carbon fibers and improving the toughness of the composite material. At the same time, the cross-linked network formed between carbon nanotubes and carbon fibers can increase the conductivity of the material, improve the particle injection capacity of the product (such as the injection of metal ions), and make the implant have antibacterial, bone induction, and bone integration capabilities while avoiding the artifact problem of traditional metal materials.
[0061] The present invention also provides a functional carbon fiber for orthopedic implants, which is prepared according to the preparation method described above.
[0062] Based on the functional carbon fiber for orthopedic implants prepared above, the present invention also provides a method for preparing a carbon fiber / polyetheretherketone composite material for an implant, comprising the following steps:
[0063] S1) compounding the polyaryletherketone and the functional carbon fiber for orthopedic implants prepared above by melt impregnation to obtain a carbon fiber polyaryletherketone prepreg;
[0064] S2) processing and molding the carbon fiber polyaryletherketone prepreg to obtain a carbon fiber / polyetheretherketone composite material for an implant.
[0065] The present invention preferably uses an extruder to melt-extrude the polyaryletherketone, and impregnates it with the treated carbon fiber at the extruder die outlet. The impregnated carbon fiber is immediately rolled, cooled, consolidated, and wound to prepare a carbon fiber polyaryletherketone prepreg.
[0066] By adjusting the extrusion speed of the extruder, the mass ratio of polyaryletherketone to carbon fiber is controlled to be 1:(1-3), preferably 1:(1.5-2.5), and more preferably 1:(1.5-2).
[0067] In the present invention, the melt index of the polyaryletherketone is 50 to 200 g / 10min, preferably 100 to 150 g / 10min, such as 50 g / 10min, 60 g / 10min, 70 g / 10min, 80 g / 10min, 90 g / 10min, 100 g / 10min, 110 g / 10min, 120 g / 10min, 130 g / 10min, 140 g / 10min, 150 g / 10min, 160 g / 10min, 170 g / 10min, 180 g / 10min, 190 g / 10min, 200 g / 10min, preferably a range value with any of the above values as the upper or lower limit. The polyaryletherketone described in the present application is a commercial polyetheretherketone, and the brand and manufacturer are not specifically limited, as long as the melt index requirements are met.
[0068] After obtaining the carbon fiber polyaryletherketone prepreg, the present invention processes and shapes it to obtain an orthopedic implant blank. According to the structural design requirements of orthopedic implant products, the carbon fiber polyaryletherketone prepreg can be prepared into orthopedic implant blank products of corresponding different structures using different processing and forming methods such as molding, pultrusion, winding, CNC (computer numerical control machine tool), etc. Since orthopedic implants have various specifications, structures and shapes, the present invention does not specifically limit and explain the processing and forming methods.
[0069] The present invention also provides a carbon fiber / polyetheretherketone composite material for an implant, which is prepared according to the preparation method described above.
[0070] The present invention provides a method for preparing functional carbon fibers for orthopedic implants, comprising the following steps: A) forming a stable carboxylated carbon nanotube aqueous dispersion; B) adding the carboxylated carbon nanotube aqueous dispersion of step A) to a polyamic acid aqueous solution with a pH value of 6.5 to 7 to obtain a sizing agent; C) impregnating the carbon fibers in the sizing agent, drying with three-stage hot rollers and hot air, and thermally imidizing the dried carbon fibers to obtain sizing carbon fibers; D) irradiating the sizing carbon fibers to obtain functional carbon fibers for orthopedic implants. The present invention adds carboxylated carbon nanotubes to the sizing agent, irradiates the sizing carbon fibers with electron beams, and hybridizes part of the carbon in the carboxylated carbon nanotubes after electron beam irradiation by sp 2 becomes sp 3 , thereby generating cross-links between adjacent carboxylated carbon nanotubes, and the carboxylated carbon nanotubes can also generate certain cross-links with the carbon fibers, thereby forming a bridging structure between the carbon fibers and improving the toughness of the composite material.
[0071] The tensile test scheme adopted in the present invention is in accordance with GB / T 3354-2014; the composite material post-impact laminate strength test scheme is in accordance with GB / T 21239-2007; and the volume resistivity test method is in accordance with GB / T1410-2006. The Ti ion implantation of the present invention is carried out by the following method: the orthopedic implant blank is placed in an ion implantation machine with a rotating intensification device, a Cu rod with a purity of 99.9% is used as the cathode working electrode, and the gas pressure in the target chamber is about 7×10 -4 Pa, the injection voltage is 45 kV, the injection pulse width is 1000 μs, the injection pulse frequency is 15 Hz, the cathode source trigger pulse width is 3000 μs, and the injection time is 15 minutes.
[0072] In order to further illustrate the present invention, a functional carbon fiber for orthopedic implants, a preparation method thereof, and a composite material for implants containing the same and a preparation method thereof provided by the present invention are described in detail below in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0073] Example 1: Preparation of functional carbon fibers for orthopedic implants
[0074] 1 mol of diamine monomer (Ⅰ) and 1 mol of dianhydride (Formula III) are dissolved in 300 mL of NMP, gradually heated to 70°C, stirred for reaction for 12 hours, and NMP is removed by vacuum distillation to obtain polyamic acid; triethylamine is added to the polyamic acid to adjust the pH value of the solution to 7, and the mass ratio of polyamic acid, carboxylated carbon nanotube aqueous dispersion and deionized water is 1:0.5:100 to obtain sizing agent 1. The preparation method of carboxylated carbon nanotubes is as follows: carbon nanotubes are mixed with nitric acid solution, the mass ratio of carbon nanotubes to nitric acid is 1:300, and the concentration of nitric acid is 1 mol / L. Heat to 55°C and react under ultrasonic conditions at an ultrasonic power of 150 W for 1 hour, then cool the product to room temperature, filter, wash and dry to obtain carboxylated carbon nanotubes;
[0075] The T800 carbon fiber was immersed in a sizing tank containing the above-mentioned sizing agent for 4 seconds, and then dried by three-stage hot rollers at temperatures of 80°C, 90°C, and 110°C and hot air at 180°C; the dried carbon fiber was treated in a vacuum furnace at 100°C, 200°C, and 310°C for 1 hour, 1.5 hours, and 1 hour, respectively, for thermal imidization treatment; the thermally imidized carbon fiber was irradiated with a 100kev electron beam with an irradiation dose of 0.5kGy to finally obtain functional carbon fiber 1 for orthopedic implants.
[0076] Example 2: Preparation of functional carbon fibers for orthopedic implants
[0077] The only difference between Example 2 and Example 1 is that "the mass ratio of polyamic acid, carboxylated carbon nanotube aqueous dispersion and deionized water is 1:1.5:100", and other conditions remain unchanged to obtain functional carbon fiber 2 for orthopedic implants.
[0078] Example 3: Preparation of functional carbon fibers for orthopedic implants
[0079] The only difference between Example 3 and Example 1 is that "the mass ratio of polyamic acid, carboxylated carbon nanotube aqueous dispersion and deionized water is 1:2:100", and other conditions remain unchanged to obtain functional carbon fiber 3 for orthopedic implants.
[0080] Example 4: Preparation of functional carbon fibers for orthopedic implants
[0081] The only difference between Example 4 and Example 1 is that "1 mol of diamine monomer (II) and 1 mol of dianhydride (Formula III) are dissolved in 300 mL of NMP", and other conditions remain unchanged to obtain functional carbon fiber 4 for orthopedic implants.
[0082] Example 5: Preparation of functional carbon fibers for orthopedic implants
[0083] The only difference between Example 5 and Example 2 is that "1 mol of diamine monomer (II) and 1 mol of dianhydride (Formula III) are dissolved in 300 mL of NMP", and other conditions remain unchanged to obtain functional carbon fiber 5 for orthopedic implants.
[0084] Example 6: Preparation of functional carbon fibers for orthopedic implants
[0085] The only difference between Example 6 and Example 3 is that "1 mol of diamine monomer (II) and 1 mol of dianhydride (Formula III) are dissolved in 300 mL of NMP", and other conditions remain unchanged to obtain functional carbon fiber 6 for orthopedic implants.
[0086] Example 7: Implant made of carbon fiber / polyetheretherketone composite material
[0087] An extruder is used to melt-extrude polyetheretherketone with a melt index of 100g / 10min at 380°C, and the polyetheretherketone prepared in Example 1 is impregnated at the outlet of the extruder die. The impregnated carbon fiber is immediately rolled on a hot pressing roller at 340°C, cooled and consolidated by hot air at 200°C, and finally wound by a winding device to prepare a carbon fiber polyaryletherketone prepreg. The mass ratio of polyaryletherketone to carbon fiber is controlled to be 1:1 by adjusting the basic speed of the extruder.
[0088] Example 8: Implant made of carbon fiber / polyetheretherketone composite material
[0089] The only difference between Example 8 and Example 7 is that "it is impregnated with the carbon fiber prepared in Example 2 at the exit of the extruder die", and other conditions remain unchanged.
[0090] Example 9: Implant made of carbon fiber / polyetheretherketone composite material
[0091] The only difference between Example 9 and Example 7 is that "it is impregnated with the carbon fiber prepared in Example 3 at the exit of the extruder die", and other conditions remain unchanged.
[0092] Example 10: Preparation of implant using carbon fiber / polyetheretherketone composite material
[0093] The only difference between Example 10 and Example 7 is that "it is impregnated with the carbon fiber prepared in Example 4 at the exit of the extruder die", and other conditions remain unchanged.
[0094] Example 11: Preparation method of carbon fiber / polyetheretherketone composite material for implant
[0095] The only difference between Example 11 and Example 7 is that "it is impregnated with the carbon fiber prepared in Example 5 at the exit of the extruder die", and other conditions remain unchanged.
[0096] Example 12: Preparation method of carbon fiber / polyetheretherketone composite material for implant
[0097] The only difference between Example 12 and Example 7 is that "it is impregnated with the carbon fiber prepared in Example 6 at the exit of the extruder die", and other conditions remain unchanged.
[0098] Example 13: Preparation method of carbon fiber / polyetheretherketone composite material for implant
[0099] An extruder is used to melt-extrude polyetheretherketone with a melt index of 100g / 10min at 380°C, and impregnated with the carbon fiber prepared in Example 5 at the outlet of the extruder die. The impregnated carbon fiber is immediately rolled on a hot pressing roller at 340°C, cooled and consolidated by hot air at 200°C, and finally wound by a winding device to prepare a carbon fiber polyaryletherketone prepreg. The mass ratio of polyetheretherketone to carbon fiber is controlled to be 1:2 by adjusting the basic speed of the extruder.
[0100] Example 14: Preparation method of carbon fiber / polyetheretherketone composite material for implant
[0101] The only difference between Example 14 and Example 13 is that "the mass ratio of polyetheretherketone to carbon fiber is controlled to be 1:3", and other conditions remain unchanged.
[0102] In order to highlight the advantages of the functional carbon fiber for orthopedic implants, comparative examples 1 and 2 were prepared. Comparative example 1 used a polyamic acid sizing agent without carboxylated carbon nanotubes, while comparative example 2 was carbon fiber that was not treated with polyamic acid and carboxylated carbon nanotube sizing agents. Performance tests highlighted the performance improvement effect of the carbon nanotube and polyamic acid composite sizing agent on the toughness and conductivity of the composite material.
[0103] Comparative Example 1
[0104] The polyaryletherketone with a melt index of 100g / 10min is melt-extruded at 380°C using an extruder, and the T800 carbon fiber is impregnated with a polyamic acid sizing agent containing a carboxylated carbon nanotube dispersion at the outlet of the extruder die. The impregnated carbon fiber is immediately rolled on a hot press roller at 340°C, cooled and consolidated by hot air at 200°C, and finally rolled up by a winding device to prepare a carbon fiber polyaryletherketone prepreg. By adjusting the basic speed of the extruder, the mass ratio of polyaryletherketone to carbon fiber is preferably 1:1. The preparation method of the polyamic acid is as follows: 1 mol of diamine monomer (Ⅰ) and 1 mol of dianhydride (Formula III) are dissolved in 300 mL of NMP, gradually heated to 70°C, stirred for reaction for 12 hours, and polyamic acid is obtained after vacuum distillation to remove NMP; triethylamine is added to the polyamic acid to adjust the pH value of the solution to 7, and the sizing agent is obtained according to the mass ratio of polyamic acid to deionized water of 1:100.
[0105] Note: The "polyamic acid sizing agent without carboxylation carbon nanotube dispersion" in Comparative Example 1 means that except for not containing carboxylation carbon nanotube dispersion, the other ingredients and preparation are the same as those of the sizing agent in Example 1.
[0106] Comparative Example 2
[0107] An extruder is used to melt-extrude polyaryletherketone with a melt index of 100g / 10min at 380°C, and impregnated with T800 carbon fiber at the outlet of the extruder die. The impregnated carbon fiber is immediately rolled on a hot pressing roller at 340°C, cooled and consolidated by hot air at 200°C, and finally wound by a winding device to prepare a carbon fiber polyaryletherketone prepreg. By adjusting the basic speed of the extruder, the mass ratio of polyaryletherketone to carbon fiber is preferably 1:1.
[0108] The tensile test specimens of Example 9, Example 12, Comparative Examples 1 and 2 were prepared to evaluate their tensile properties. The above-mentioned Example 9, Example 10, Comparative Examples 1 and 2 were processed and molded to obtain knee joints by injection molding, and their particle injection ability and bone integration ability were tested.
[0109] Table 1 gives the tensile strength of Example 9, Example 12, Comparative Examples 1 and 2 in the 0° direction. It can be found from the table that the strength and fracture toughness of the polyetheretherketone composite material (Comparative Example 1) prepared by using carbon fiber treated with polyamic acid containing carbon nanotube dispersion liquid without carboxylation are better than those of the polyetheretherketone composite material (Comparative Example 2) prepared by using carbon fiber. The strength and toughness of the polyetheretherketone composite material of carbon fiber treated with polyamic acid containing carboxylation carbon nanotube dispersion liquid have been greatly improved. The tensile strength of Example 9 is 2500MPa and the elongation at break is 1.4%; the tensile strength and elongation at break of Example 12 are 2400MPa and 1.4%, respectively. In addition, it can be found from Table 1 that compared with Comparative Examples 1 and 2, the post-impact compression strength of Examples 9 and 12 has been greatly improved, reaching 340MPa and 330MPa, respectively, showing higher impact resistance and increasing the durability of the composite material. Therefore, considering the tensile strength, fracture toughness and post-impact compression strength of the composite material, Example 9 has the best performance.
[0110] Table 1 Tensile properties of Example 9, Example 12, Comparative Example 1 and Comparative Example 2
[0111] sample Tensile Strength Elongation at break Compression strength after impact Example 9 2500MPa 1.4% 340MPa Example 12 2400MPa 1.4% 330MPa Comparative Example 1 2100MPa 0.8% 300MPa Comparative Example 2 1900MPa 0.7% 260MPa
[0112] Table 2 gives the volume resistivity of Example 9, Example 12, Comparative Example 1 and Comparative Example 2. It can be found from the table that the volume resistivity of the polyetheretherketone composite material of carbon fiber treated with polyamic acid containing carboxylated carbon nanotube dispersion is greatly reduced. This is because the carbon nanotubes form a conductive network therein, which increases the conductivity of the material and reduces the volume resistivity of the material.
[0113] Table 2 Volume resistivity of Example 9, Example 12, Comparative Example 1 and Comparative Example 2
[0114]
[0115]
[0116] Table 3 shows the surface element table of Example 9, Example 12, Comparative Example 1 and Comparative Example 2. After Ti ion implantation for the same time, Example 9 has the highest Ti content. This is because Example 9 has a higher conductivity, which can help eliminate the influence of accumulated charge on ion implantation and enhance the ion implantation capability of the material.
[0117] Table 3 Surface element contents of Example 9, Example 12, Comparative Example 1 and Comparative Example 2
[0118] sample Example 9 Example 12 Comparative Example 1 Comparative Example 2 C (wt%) 86.4 86.6 86.8 87 O(wt%) 11.5 11.5 11.4 12.6 N (wt%) 0.9 0.9 1.0 0 Ti(wt%) 1.2 1.0 0.8 0.4
[0119] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon fiber / polyetheretherketone composite material for an implant, comprising the following steps: A) forming a stable carboxylated carbon nanotube aqueous dispersion of the carboxylated carbon nanotubes; B) adding the carboxylated carbon nanotube aqueous dispersion obtained in step A) to a polyamic acid aqueous solution having a pH value of 6.5 to 7 to obtain a sizing agent; C) After the carbon fiber is impregnated in a sizing agent, it is dried by three-stage hot rollers and hot air, and the dried carbon fiber is thermally imidized to obtain sized carbon fiber; The thermal imidization is a three-stage programmed temperature increase, wherein the temperature of the first stage thermal imidization is 80-120°C; the temperature of the second stage thermal imidization is 180-220°C; and the temperature of the third stage thermal imidization is 280-320°C; D) irradiating the sized carbon fiber to obtain functional carbon fiber for orthopedic implants; The irradiation treatment in step D) is electron beam irradiation treatment, the energy of the electron beam irradiation is 50-200kev, and the dose of the electron beam irradiation is 0.1-1kGy; E) compounding the polyetheretherketone and the functional carbon fiber for orthopedic implants by a melt impregnation method to obtain a carbon fiber polyetheretherketone prepreg; F) processing and molding the carbon fiber polyetheretherketone prepreg to obtain a carbon fiber / polyetheretherketone composite material for an implant.
2. The preparation method according to claim 1, characterized in that: The polyamic acid aqueous solution with a pH value of 6.5 to 7 is prepared according to the following steps: In a reaction container with a nitrogen protection device, diamine and dianhydride are mixed in a molar ratio of 1:(0.9-1.1) and then mixed with a solvent, and stirred at 0-10° C. for 1-2 hours; the obtained solution is freed of the solvent to obtain polyamic acid, the polyamic acid is added into deionized water and stirred, an organic amine is added, and the pH value is adjusted to 6.5-7 to obtain a polyamic acid aqueous solution; The diamine has a structure shown in Formula I and / or Formula II: The dianhydride has a structure shown in Formula III:
3. The preparation method according to claim 2, characterized in that: The mass ratio of the polyamic acid, the carboxylated carbon nanotube aqueous dispersion and deionized water is 1:(0.5-2):(80-120).
4. The preparation method according to claim 1, characterized in that: The average diameter of the carbon fibers in step C) is 4-8 μm.
5. The preparation method according to claim 1, characterized in that: The temperatures of the three-stage hot rollers are 75-85°C, 85-95°C, and 105-115°C, respectively.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the functional carbon fiber for orthopedic implants to polyetheretherketone is 1:(1-3); The melt index of the polyetheretherketone is 50 to 200 g / 10 min.
7. A carbon fiber / polyetheretherketone composite material for an implant, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
A method for preparing carbon nanotube / polyacrylic acid hydrogel, its products and applications
CN114031710B
Preparation method of carbon fiber enhanced polyimide based composite material
CN109265998A
Carboxylated carbon nanotube / polyimides composite film and preparation method thereof
CN109929129A
Carbon nanoparticle / epoxy resin interface reinforced electron beam radiation-induced crosslinking method and obtained cured resin
CN115304799A